THU0349 AUTOLOGOUS FAT GRAFTING IN THE TREATMENT OF PATIENTS WITH SYSTEMIC SCLEROSIS: CURRENT EXPERIENCE AND FUTURE PROSPECTS. (June 2019) - Spinella, Amelia; Pignatti, Marco; Citriniti, Giorgia; Lumetti, Federica; Cocchiara, Emanuele; Palermo, Adalgisa; Sighinolfi, Gianluca; Pacchioni, Lucrezia; Zaccaria, Giovanna; Lusetti, Irene Laura; Santis, Giorgio De; Salvarani, Carlo; et al.
Abstract : Background: Systemic Sclerosis (SSc) is a connective tissue disease, characterized by endothelial dysfunction and fibrosis, potentially affecting internal organs and reducing life expectancy. Digital ulcers (DUs), as well as hand and face skin thickening, are the hallmarks of the disease. These alterations lead to pain, functional impairment, aesthetic damages, and psychological distress. Autologous fat grafting (AFG) is a surgical technique used also to promote tissue regeneration. In the last decade, AFG has been successfully developed to treat clinical conditions characterized by skin atrophy or fibrosis. AFG composition of multipotent cells, carrying angiogenic, and immunogenic properties, may be able to restore the damaged tissues. Objectives: Evaluate our experience with AFG to treat and prevent damage and disability due to DUs and SSc skin complications. Methods: We analyzed 25 SSc patients, extrapolated from a larger series of 45 subjects, complaining about mouth and/or hand impairment, due to skin involvement, and, in some cases, long-lasting DUs (M/F 6/19, mean age 55.69±9.25-SD-years, mean disease duration 184.68±121.09-SD-months, L/D cutaneous subsets 21/4). Surgical procedures consisted in the injection of centrifuged and purified autologous fat, harvested from hips or abdomen. 2ml of fat were grafted in each of the 8 sites around the mouth, while 0.5 or 1 ml around the neurovascular bundle at the base of each finger. The study included: preoperative data collection; 2 or 3 surgical sessions at a distance of 6 months one from the other; data collection at 3 months after each surgical session; data collection at 3 and 6 months of follow up-FU after the last surgical procedure. Data collection consisted of clinic-serological SSc features and clinimetric measures about hand and mouth, if present DUs were assessed as well. Furthermore, patients were asked to fill in questionnaires in order to express their level of satisfaction with hand and mouth functionality. Results: Overall 63 surgical procedures were performed. After 1 to 3 procedures, patients reported an improvement of perioral skin tension (p=0.0238) and a reduced dry mouth feeling (p=0.0269). Similarly, patients stated an improvement of hands tension (p=0.0037). Furthermore, we observed a complete healing of DUs in 8/9 patients (p=0.0297). These positive clinical changes were mirrored by a subjective amelioration. In particular, pain decreased, evaluated by short-form McGill Pain Questionnaire (SF-MPQ), scrutinizing sensory (p=0.3340) and affective (p=0.2234) descriptors. The perception of disability improved too, showing an amelioration trend in Health Assessment Questionnaire-HAQ (p=0.4301) and Mouth Handicap in Systemic Sclerosis scale-MHISS- (p=0.9775). Conclusion: Our results confirm the potential efficacy of AFG to treat SSc skin complications and DUs. We reported an almost complete healing of DUs and a promising improvement of skin thickness and hardness both at hands and mouth, with good safety profiles. These clinical results were reflected by the subjective improvement of patients' well-being. Population enlargement and extended FU is ongoing to identify more responsive SSc subsets. Long term results with soft tissue biopsies will give us further data to finally evaluate the efficacy of this approach that aims to improve the care and quality of life of our SSc patients. Disclosure of Interests: None declared